CE‐MS for the analysis of intact proteins 2010–2012. Issue 1 (3rd December 2012) - Haselberg, Rob; de Jong, Gerhardus J.; Somsen, Govert W.; Rassi, Ziad El
<x xml:space="preserve">Abstract</x> Since its introduction in 1987, CE‐MS has become an increasingly important technique for the analysis of biomolecules. Since our previous update on CE‐MS methods within the field of intact protein analysis (Electrophoresis 2011, 32, 66–82), a variety of interesting methodological improvements and applications have been reported in literature. Therefore, this article presents an overview of the development and application of CE‐MS for intact protein analysis as published between June 2010 and June 2012. The article is divided in sections that treat CE coupled to MS through ESI, MALDI, and ICP ionization, respectively. In the section about CE‐ESI‐MS, technological developments with respect to CE‐MS interfacing, prevention of protein adsorption, and chip‐based CE‐MS are treated in more detail. Novel interfacing strategies and the development of improved capillary coating strategies appeared to be the major developments. Furthermore, in all sections, the applicability of CE‐MS for intact protein analysis is demonstrated by representative examples, including important developments in the fields of biopharmaceutical characterization and the analysis of proteins in biological samples. Finally, some general conclusions and future perspectives are given.